KOMUNITAS-SEMINARI DIASPORA DALAM MASA PANDEMIC COVID-19 (Reaktif-Reflektif Atas Yoh 20:17) - Donatus Dole (Aggiornamento, 2020)
The timing of the outbreak was never suspected. Likewise, the vocation. Both will appear by themselves and suddenly. There is a big difference betwen, that the outbreak is expected to disappear quickly but the vocation are expected to be maintained. For this reason, the community of Interdiocesan Major Seminary "San Giovanni XXIII" Malang determines a way to keep the vocation through the spread of the all seminarians to several diaspora communities in the retreat houses of the diocese of Malang. This article was created to reflect the situation; first, the corona virus outbreak; secondly, the dinamic of the life's vocation, both the seminarians and the formators at Mayor of Seminary Giovanni.